TRPV1 Is Associated with Testicular Apoptosis in Mice - Adrian S. Siregar; Marie Merci Nyiramana; Eun-Jin Kim; Eui-Jung Shin; Chang-Woon Kim; Dong Kun Lee; Seong-Geun Hong; Jaehee Han; Dawon Kang (The Korean Society of Animal Reproduction and Biotechnology, 2019)
Reproductive potential decreases with age. A decrease in male fertility is due to a combination of morphological and molecular alterations in the testes. Transient receptor potential vanilloid receptor-1 (TRPV1) is associated with aging and lifespan, and its activation causes apoptotic cell death in various cell types. However, the effect of TRPV1 on testicular apoptosis in aged mice has not yet been reported. TRPV1 knockout (KO) mice had a longer lifespan than that of wild-type (WT) mice. Lifespan was increased by 11.8% in male TRPV1 KO mice compared to that in WT mice. TRPV1 KO males lived approximately 100 days longer than WT males on average, and the maximum lifespan was markedly extended in TRPV1 KO mice compared with that in WT mice. The TRPV1 expression levels were highly increased in the testes of older mice. TRPV1 was expressed in the entire testes region of the old mice. In addition, old TRPV1 KO mice had lower testicular apoptosis than that of WT mice. Our results show that TRPV1 induces testicular apoptosis and suggest that TRPV1 may be associated with testicular aging.